PENGARUH PERSEPSI MANFAAT, PERSEPSI KEMUDAHAN, FITUR LAYANAN, DAN KEPERCAYAAN TERHADAP MINAT MENGGUNAKAN E-MONEY CARD (STUDI PADA PENGGUNA JASA COMMUTERLINE DI JAKARTA) - Wibowo, Setyo Ferry; Rosmauli, Dede; Suhud, Usep (Fakultas Ekonomi, Universitas Negeri Jakarta, 2015)
PENGARUH PERSEPSI MANFAAT, PERSEPSI KEMUDAHAN, FITUR LAYANAN, DAN KEPERCAYAAN TERHADAP MINAT MENGGUNAKAN E-MONEY CARD (STUDI PADA PENGGUNA JASA COMMUTERLINE DI JAKARTA)Setyo Ferry WibowoFakultas Ekonomi Universitas Negeri Jakartae-mail : setyoferry@yahoo.comDede RosmauliFakultas Ekonomi Universitas Negeri Jakartae-mail : dederosmauli@gmail.comUsep SuhudFakultas Ekonomi Universitas Negeri Jakartae-mail : usepsuhud@feunj.ac.idABSTRACTThe purpose of this research are: to know influential positive and significant perceived usefulness toward intention to use e-money card, to know influential positive and significant perceived ease of use toward intention to use e-money card, to know influential positive and significant feature availability toward intention to use e-money card, to know influential positive and significant terust toward intention to use e-money card. Object of the research is respondent that has not using e-money card. The result of descriptive test shows; the significant influence of perceived usefulness toward intention to use e-money card, the significant influence of perceived ease of use toward intention to use e-money card, the significant influence of feature availability toward intention to use e-money card and the significant influence of trust toward intention to use e-money card.Keywords: perceived usefulness, perceived ease of use, feature availability,trust, and intention to use e-money card.